Negative electrode composition, negative electrode for lithium secondary battery including the same, and lithium secondary battery including the negative electrode
A negative electrode composition with silicon-based active materials and planar/linear conductive materials addresses the volume expansion issue in silicon-based batteries, improving electrical connectivity and cycle stability while maintaining high energy density.
Patent Information
- Application Number
- JP2024541704
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-21
- Filing Date
- 2023-09-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-09-21
AI Technical Summary
Silicon-based active materials in lithium secondary batteries experience rapid volume expansion during charging and discharging, leading to conductive path disruption and reduced battery performance, making it difficult to achieve high energy density and cycle stability.
A negative electrode composition using silicon-based active materials with specific crystal grain sizes and a combination of planar and linear conductive materials to enhance electrical connectivity and prevent isolation, eliminating the need for dotted conductive materials.
The solution improves the life and electrical connectivity of the negative electrode, maintaining high energy density and reducing gas generation at high temperatures, thereby enhancing the battery's cycle performance and output characteristics.
Smart Images

Figure 2025502176000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0119283, filed with the Korean Intellectual Property Office on September 21, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode. [Background technology]
[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields as part of this is power generation and storage using electrochemical reactions.
[0004] At present, a representative example of an electrochemical element that utilizes such electrochemical energy is a secondary battery, and the range of its use is tending to expand more and more.
[0005] As technological development and demand for mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. In addition, research into a method for manufacturing a high-density electrode with a higher energy density per unit volume as an electrode for such high-capacity lithium secondary batteries is being actively conducted.
[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode. Silicon-based particles having a large discharge capacity can be used as the negative electrode active material.
[0007] In particular, in recent years, in response to the demand for high-density energy batteries, active research has been conducted into methods of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. However, silicon-based compounds, which are high-capacity materials, have a large capacity compared to the conventionally used graphite, but they have the problem that their volume suddenly expands during charging, cutting off the conductive path and reducing the battery characteristics.
[0008] Therefore, in order to solve the problems when using silicon-based compounds as negative electrode active materials, various methods for suppressing the volume expansion itself or preventing the conductive path from being broken, such as a method for adjusting the driving potential, a method for further coating a thin film on the active material layer, and a method for adjusting the particle size of the silicon-based compound, have been discussed. However, the above methods have limitations in their application because they may actually degrade the performance of the battery, and there are still limitations in the commercialization of negative electrode batteries with a high content of silicon-based compounds.
[0009] In addition, when a negative electrode is made using a silicon-based active material to increase energy density, it is difficult to realize sufficient cycle performance by using a small amount of dot-shaped conductive material as in the case of existing carbon-based active material systems due to high swelling during charging and discharging. Therefore, when an excessive amount of dot-shaped conductive material is used, there is room for improvement in life performance, but there is a limit, and the high specific surface area of the dot-shaped conductive material causes problems such as an increase in slurry viscosity and an increase in gas generation at high temperatures.
[0010] Therefore, even when silicon-based compounds are used as active materials to improve capacity performance, research is needed into conductive material systems that can prevent the conductive paths from being damaged due to the volume expansion of the silicon-based compounds and that are particularly suitable for crystalline silicon-based active materials, which are high-capacity negative electrode materials. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Japanese Patent Application Laid-Open No. 2009-080971 SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION
[0012] Recognizing the above problems, as a result of research on the conductive material system to reduce the gas generation amount at high temperatures, instead of using a dot-shaped conductive material for a silicon-based active material that satisfies a certain crystal grain size, when applying a bulk conductive material and a linear conductive material, it has been found that the electrical connectivity can be improved and the electrical isolation phenomenon can be prevented.
[0013] Accordingly, the present application relates to a negative electrode composition, a negative electrode for a lithium secondary battery including the same, and a lithium secondary battery including the negative electrode. MEANS FOR SOLVING THE PROBLEMS
[0014] One embodiment of the present specification is a negative electrode composition including a silicon-based active material; a negative electrode conductive material; and a negative electrode binder, wherein the silicon-based active material includes at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 <x <2), based on 100 parts by weight of the silicon-based active material, the SiOx (x = 0) is included in an amount of 70 parts by weight or more, the silicon-based active material has a crystal grain size of 200 nm or less, and the negative electrode conductive material includes a bulk conductive material; and a linear conductive material.
[0015] In another embodiment, there is provided a negative electrode for a lithium secondary battery including a negative electrode current collector layer; and a negative electrode active material layer including the negative electrode composition according to the present application formed on one or both surfaces of the negative electrode current collector layer.
[0016] Finally, there is provided a lithium secondary battery including a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte. EFFECTS OF THE INVENTION
[0017] In one embodiment of the present invention, a negative electrode composition is prepared by using a crystalline silicon-based active material having a specific range to increase the energy density. In this case, the negative electrode conductive material is a planar conductive material and a linear conductive material, which greatly improves the electrical connectivity between the silicon-based active materials, thereby preventing electrical isolation that may occur when charging / discharging a negative electrode using a silicon-based active material, thereby improving the life of the negative electrode.
[0018] In the case of a negative electrode using a conventional carbon-based active material, a small amount of dot-like conductive material was used as the negative electrode conductive material, but when such dot-like conductive material is applied to the silicon-based active material of the present invention, it is difficult to realize sufficient cycle performance, and when an excessive amount of dot-like conductive material is included, although there is room for improvement in life performance, problems occur in the viscosity increase of the composition and the amount of high-temperature gas generated due to the high specific surface area. In other words, the negative electrode composition of the present application is mainly characterized by constructing a system that can be applied together with a high-energy density silicon-based active material by applying the specific composition and content of the above-mentioned negative electrode conductive material without using a dot-like conductive material. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. [Diagram 2] FIG. 1 is a diagram showing a stacked structure of a lithium secondary battery according to an embodiment of the present application. [Diagram 3] 1 shows an expanded view of a silicon-based active material according to one embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Before describing the present invention, some terms will first be defined. In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.
[0021] In this specification, "p to q" means a range of "not less than p and not more than q". In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the above-mentioned measurement method.
[0022] In this specification, "Dn" means particle size distribution, and refers to the particle size at the n% point of the cumulative particle number distribution by particle size. That is, D50 is the particle size (average particle size) at the 50% point of the cumulative particle number distribution by particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution by particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution by particle size. On the other hand, the particle size distribution may be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the difference in the diffraction pattern due to the particle size when the particles pass through a laser beam is measured to calculate the particle size distribution.
[0023] In this specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer is involved in a polymerization reaction and is contained as a repeating unit in the polymer. In this specification, when a polymer contains a monomer, this is interpreted as the same as when a polymer contains a monomer as a monomer unit.
[0024] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers, unless otherwise specified as a "homopolymer."
[0025] In this specification, the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are the polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various degrees of polymerization commercially available for molecular weight measurement as standard substances. In this specification, the molecular weight means the weight-average molecular weight unless otherwise specified.
[0026] Hereinafter, for those with ordinary knowledge in the technical field to which the present invention pertains to easily implement the present invention, a detailed description will be given with reference to the drawings. However, the present invention can be implemented in various different forms and is not limited to the following description.
[0027] One embodiment of this specification is a negative electrode composition containing a silicon-based active material; a negative electrode conductive material; and a negative electrode binder, wherein the silicon-based active material has a crystal grain size of 200 nm or less, and the negative electrode conductive material includes a planar conductive material; and a linear conductive material, and provides a negative electrode composition.
[0028] One embodiment of this specification is a negative electrode composition containing a silicon-based active material; a negative electrode conductive material; and a negative electrode binder, wherein the silicon-based active material includes at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), based on 100 parts by weight of the silicon-based active material, contains 70 parts by weight or more of the SiOx (x = 0), the silicon-based active material has a crystal grain size of 200 nm or less, and the negative electrode conductive material includes a planar conductive material; and a linear conductive material, and provides a negative electrode composition.
[0029] In one embodiment of the present application, a negative electrode composition is provided, wherein the silicon-based active material includes at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, contains 70 parts by weight or more of the SiOx (x = 0).
[0030] In another embodiment, the silicon-based active material may contain 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more of the SiOx (x=0) based on 100 parts by weight of the silicon-based active material, and may contain 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0031] In one embodiment of the present application, the silicon-based active material may be a silicon-based active material that contains pure silicon (Si) particles. The use of pure silicon (Si) particles as the silicon-based active material may mean that the silicon-based active material contains pure Si particles (SiOx (x=0)) that are not bonded with other particles or elements, based on 100 parts by weight of the total silicon-based active material, in the above range.
[0032] In one embodiment of the present application, the silicon-based active material may be composed of silicon-based particles having 100 parts by weight of SiOx (x=0).
[0033] In one embodiment of the present application, the silicon-based active material may contain metal impurities. In this case, the impurities are metals that may be generally contained in silicon-based active materials, and specifically, the impurities may contain 0.1 parts by weight or less based on 100 parts by weight of the silicon-based active material.
[0034] Silicon-based active materials have a significantly higher capacity than the graphite-based active materials that have been used conventionally, and there have been increasing efforts to use them. However, because of their high volume expansion during charging and discharging, they have only been used in small amounts mixed with graphite-based active materials.
[0035] However, the negative electrode composition according to the present invention employs a silicon-based active material whose crystal grain size satisfies the range described below, and contains a specific planar conductive material and linear conductive material, thereby improving the life performance of the negative electrode and reducing the amount of gas at high temperatures.
[0036] In one embodiment of the present application, the crystal grain size of the silicon-based active material may be 200 nm or less.
[0037] In the present application, the crystal grain size of the silicon-based active material may be 10 nm or more and 150 nm or less.
[0038] In another embodiment, the crystal grain size of the silicon-based active material may be 200 nm or less, preferably 130 nm or less, more preferably 110 nm or less, even more preferably 100 nm or less, specifically 95 nm or less, more specifically 91 nm or less. The crystal grain size of the silicon-based active material may be 10 nm or more, preferably 15 nm or more, more preferably 30 nm or more.
[0039] The silicon-based active material has the above-mentioned crystal grain size, and the crystal grain size of the silicon-based active material can be adjusted by changing the process conditions in the manufacturing process. In this case, by satisfying the above-mentioned range, the crystal grain boundary is widely distributed, and lithium ions are uniformly inserted during insertion, and the stress applied during lithium ion insertion into silicon particles can be reduced, thereby alleviating particle cracking. As a result, the negative electrode has the characteristic of improving the life stability. If the crystal grain size exceeds the above-mentioned range, the crystal grain boundary in the particle is narrowly distributed, in which case lithium ions are non-uniformly inserted in the particle, and the stress due to ion insertion is large, resulting in particle cracking.
[0040] FIG. 3 shows an enlarged view of a silicon-based active material according to an embodiment of the present application. Specifically, the silicon-based active material 1 is composed of a number of crystalline structures 2, and it can be seen that the crystalline structures have a crystalline grain distribution of 1 nm to 200 nm. In addition, the space between the crystalline structures can be defined as a grain boundary. In addition, the crystalline structure can generally be expressed as a grain.
[0041] In one embodiment of the present application, there is provided a negative electrode active material, wherein the silicon-based active material includes a crystalline structure having a crystal grain distribution of 1 nm or more and 200 nm or less, and the area ratio of the crystalline structure is 5% or less based on the total area of the silicon-based active material.
[0042] In still another embodiment, the area ratio of the crystalline structure may be 5% or less, 3% or less, or 0.1% or more, based on the total area of the silicon-based active material.
[0043] That is, the silicon-based active material according to the present application has a crystal grain size of 200 nm or less, and the size of each crystal structure is small, so that the above-mentioned area ratio can be satisfied, and thus the distribution of the grain boundaries can be broadened, thereby achieving the above-mentioned effects.
[0044] In one embodiment of the present application, there is provided a negative electrode active material, in which the silicon-based active material contains 20 or more crystal structures.
[0045] In another embodiment, the number of crystalline structures contained in the silicon-based active material may be 20 or more, 30 or more, or 35 or more, and may be in the range of 60 or less, or 50 or less.
[0046] That is, as described above, when the silicon-based active material has a crystal grain size that satisfies the above range and the number of crystal structures that satisfies the above range, the strength of the silicon-based active material itself will have an appropriate range, and when contained in an electrode, it will be able to provide flexibility and have the characteristic of being able to efficiently suppress volume expansion.
[0047] In this application, the term "crystal grain" refers to a crystal grain in a metal or material that is an aggregate of microscopic irregular shapes, and the term "crystal grain size" can refer to the diameter of an observed crystal grain. That is, in this application, the term "crystal grain size" refers to the size of a domain that shares the same crystal orientation within a grain, and has a different concept from the grain size or particle size that represents the size of a substance.
[0048] In one embodiment of the present application, the crystal grain size can be calculated as a FWHM (Full Width at Half Maximum) value through XRD analysis. The remaining values except L are measured through XRD analysis of the silicon-based active material, and the crystal grain size can be measured based on the fact that FWHM and crystal grain size are inversely proportional to each other through the Debey-Scherrer equation. In this case, the Debey-Scherrer equation is as shown in the following Equation 1-1.
[0049] [Formula 1-1] FWHM=Kλ / LCosθ In the above formula 1-1, L is the grain size, K is a constant, θ is the Bragg angle, and λ is the wavelength of the X-ray.
[0050] The crystal grains may have various shapes and may be measured three-dimensionally. Generally, the size of the crystal grains may be measured by a commonly used circle method or diameter measurement method, but is not limited thereto.
[0051] The diameter measurement method involves drawing 5 to 10 parallel lines, each with a length of L mm, on a micrograph of the target particle, counting the number of crystal grains z on the lines, and averaging them. At this time, only those that are entirely contained are counted, and those that are on the lines are excluded. If the number of lines is P and the magnification is V, the average particle diameter can be calculated using the following formula 1-2.
[0052] [Formula 1-2] Dm = (L*P*10 3 ) / (zV)(μm)
[0053] The circle method is a method in which a circle of a specified diameter is drawn on a micrograph of a target particle, and then the average area of the crystal grains is calculated based on the number of crystal grains that fall within the circle and the number of crystal grains that cross the boundary line, and can be calculated using the following formula 1-3.
[0054] [Formula 1-3] Fm = (Fk * 10 6 ) / ((0.67n+z)V 2 )(μm 2 ) In the above formula 1-3, Fm is the average particle area, Fk is the measured area on the photograph, z is the number of particles that fit inside the circle, n is the number of particles that span the circular arc, and V is the magnification of the microscope.
[0055] One embodiment of the present application is a surface area of 0.25 m 2 / g or more of a silicon-based active material.
[0056] In yet another embodiment, the silicon-based active material has a surface area of 0.25 m 2 / g or more, preferably 0.28m 2 / g or more, more preferably 0.30m 2 / g or more, specifically 0.31m 2 / g or more, more specifically 0.32m 2 The silicon-based active material may have a surface area of 3 m 2 / g or less, preferably 2.5m 2 / g or less, more preferably 2.2m 2 The surface area can be measured according to DIN 66131 (using nitrogen) in accordance with the following ranges:
[0057] In one embodiment of the present application, the negative electrode active material has a surface area of 0.30 m 2 / g or more 4.00m 2 / g or less.
[0058] In yet another embodiment, the silicon-based active material has a surface area of 0.30 m 2 / g or more, preferably 0.31m 2 / g or more, more preferably 0.32m 2 The silicon-based active material may have a surface area of 4.00 m 2 / g or less, preferably 2.50m 2 / g or less, more preferably 2.20m 2 / g or less.
[0059] The silicon-based active material has the above surface area, and the size of the surface area of the silicon-based active material can be adjusted by changing the process conditions in the manufacturing process and the growth conditions of the silicon-based active material. That is, when the negative electrode active material is manufactured by the manufacturing method according to the present application, the surface area is larger than that of particles having the same particle size due to the rough surface, and in this case, the above range is satisfied, and the binding force with the binder is increased, so that the cracks in the electrode caused by repeated charge and discharge cycles can be reduced.
[0060] In addition, lithium ions are inserted uniformly during insertion, so that the stress applied when lithium ions are inserted into silicon particles can be reduced, and thus particle cracking can be alleviated. As a result, the negative electrode has the characteristic of improving its life stability. If the surface area size is less than the above range, even if the particles have the same particle size, the surface is formed smoothly, and the binding force with the binder is reduced, causing electrode cracks. In this case, lithium ions in the particles are inserted non-uniformly, and the stress caused by ion insertion is large, causing particle cracking.
[0061] In one embodiment of the present application, the silicon-based active material may satisfy the range of the following formula 2-1.
[0062] [Formula 2-1] X1 / Y1≦0.960 In the above formula 2-1, X1 is the actual area of the silicon-based active material, Y1 means the area of a spherical particle having the same periphery as the silicon-based active material.
[0063] The formula 2-1 can be measured using a particle analyzer. Specifically, the silicon-based active material according to the present application is scattered on a glass plate by injecting air, and then a shadow image of the scattered silicon-based active material particles is taken to measure the particle shapes of 10,000 silicon-based active material particles in the photograph. In this case, the formula 2-1 is a value representing the average for 10,000 particles. From the image, the formula 2-1 according to the present application can be measured, and the formula 2-1 can be expressed as the circularity of the silicon-based active material. The sphericity can be calculated according to the formula [4π*actual area of silicon-based active material / (boundary) 2 ] may also be expressed as:
[0064] In one embodiment of the present application, the sphericity of the silicon-based active material may be, for example, 0.960 or less, for example, 0.957 or less. The sphericity of the silicon-based active material may be, for example, 0.8 or more, for example, 0.9 or more, specifically 0.93 or more, more specifically 0.94 or more, for example, 0.941 or more.
[0065] In one embodiment of the present application, the silicon-based active material may satisfy the range of the following formula 2-2.
[0066] [Formula 2-2] X2 / Y2≦0.996 In the above formula 2-2, Y2 is the actual perimeter of the silicon-based active material, X2 is the perimeter of the circumscribing figure of the silicon-based active material.
[0067] The formula 2-2 can be measured using a particle analyzer. Specifically, the silicon-based active material according to the present application is scattered on a glass plate by air injection, and then a shadow image of the scattered silicon-based active material particles is taken to measure the particle shapes of 10,000 silicon-based active material particles in the photograph. In this case, the formula 2-2 is a value representing the average for 10,000 particles. The formula 2-2 according to the present application can be measured from the image, and the formula 2-2 can be expressed as the convexity of the silicon-based active material.
[0068] In one embodiment of the present application, the range of X2 / Y2≦0.996, preferably X2 / Y2≦0.995, may be satisfied, and the range of 0.8≦X2 / Y2, preferably 0.9≦X2 / Y2, more preferably 0.95≦X2 / Y2, specifically 0.98≦X2 / Y2 may be satisfied.
[0069] The smaller the value of the formula 2-1 or 2-2, the greater the roughness of the silicon-based active material. By using a silicon-based active material having the above range, the bonding strength with the binder is increased, and thus cracks in the electrode caused by repeated charge / discharge cycles can be alleviated.
[0070] On the other hand, the average particle size (D50) of the silicon-based active material of the present invention may be 3 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is within the above range, the specific surface area of the particles is within an appropriate range, and the viscosity of the negative electrode slurry is formed within an appropriate range. This allows smooth dispersion of the particles constituting the negative electrode slurry. In addition, when the size of the silicon-based active material is equal to or greater than the above lower limit range, the complex of the conductive material and the binder in the negative electrode slurry has an excellent contact area between the silicon particles and the conductive material, and the conductive network is more likely to be maintained, thereby increasing the capacity retention rate. On the other hand, when the average particle size satisfies the above range, silicon particles that are too large are excluded, and the surface of the negative electrode is formed smoothly, thereby preventing the non-uniformity of the current density during charging and discharging.
[0071] In one embodiment of the present application, the silicon-based active material may be, for example, in crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or spheroidal particles. Alternatively, but less preferably, the silicon particles may also have a fibrous structure or be in the form of a silicon-containing film or coating.
[0072] In one embodiment of the present application, a negative electrode composition is provided in which the silicon-based active material is 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.
[0073] In another embodiment, the silicon-based active material may comprise 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, based on 100 parts by weight of the negative electrode composition, and may comprise 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 85 parts by weight or less.
[0074] The negative electrode composition according to the present application uses a silicon-based active material with extremely high capacity within the above range, and by using a specific conductive material and binder that suppress the volume expansion rate during charge and discharge, the performance of the negative electrode is not reduced even when the above range is included, and the negative electrode composition has the characteristic of excellent output characteristics during charge and discharge.
[0075] In one embodiment of the present application, the silicon-based active material may have a non-spherical morphology, and the sphericity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0076] In this application, the circularity is determined by the following formula 3-1, where A is the area and P is the perimeter. [Formula 3-1] 4πA / P 2
[0077] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but in recent years, as the demand for high-capacity batteries has increased, there have been increasing attempts to mix silicon-based compounds to increase capacity. However, silicon-based compounds have a limitation in that their volume expands rapidly during the charge / discharge process, damaging the conductive path formed in the negative electrode active material layer and reducing the performance of the battery.
[0078] Therefore, the negative electrode conductive material according to one embodiment of the present application may include a sheet conductive material and a linear conductive material.
[0079] As described above, the negative electrode conductive material includes a planar conductive material and a linear conductive material, which greatly improves the electrical connectivity between the silicon-based active material particles and prevents the silicon-based active material particles from being isolated during charging / discharging, thereby improving the life performance of the negative electrode.
[0080] In one embodiment of the present application, the negative electrode conductive material may include a sheet conductive material. The planar conductive material can improve conductivity by increasing surface contact between silicon particles in the negative electrode, and at the same time, can suppress the disconnection of the conductive path due to volume expansion, and can be expressed as a plate-type conductive material or a bulk-type conductive material.
[0081] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may be preferably platelet graphite.
[0082] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. If the range is satisfied, the sufficient particle size makes it easy to disperse without causing an excessive increase in the viscosity of the negative electrode slurry. Therefore, when dispersing using the same equipment and time, the dispersion effect is excellent.
[0083] In one embodiment of the present application, the sheet conductive material provides a negative electrode composition having a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 6.0 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.
[0084] In one embodiment of the present application, the sheet conductive material may be a graphite-based plate-like material. In one embodiment of the present application, the sheet conductive material may be a sheet conductive material having a high BET specific surface area; or a sheet conductive material having a low specific surface area.
[0085] In one embodiment of the present application, the sheet conductive material may be a high-specific surface area sheet conductive material or a low-specific surface area sheet conductive material without any restrictions. However, since the sheet conductive material in the present application may be affected to some extent by dispersion in terms of electrode performance, it may be particularly preferable to use a low-specific surface area sheet conductive material that does not cause dispersion problems.
[0086] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of 5 m 2 / g or more.
[0087] In another embodiment, the sheet conductive material has a BET specific surface area of 5 m 2 / g or more 500m 2 / g or less, preferably 5m 2 / g or more 300m 2 / g or less, more preferably 5m 2 / g or more 250m 2 / g or less.
[0088] In another embodiment, the sheet conductive material is a high specific surface area sheet conductive material having a BET specific surface area of 50 m 2 / g or more 500m 2 / g or less, preferably 80m 2 / g or more 300m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less.
[0089] In another embodiment, the sheet conductive material is a sheet conductive material having a low specific surface area and a BET specific surface area of 5 m 2 / g or more 40m 2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m 2 / g or less.
[0090] In the present application, the sheet conductive material may have a thickness that falls within the range of 0.5 μm or more and 2 μm or less.
[0091] In the present application, the sheet conductive material may have a ratio of D50 to the thickness of 20% to 30%. In this case, the ratio of D50 to the thickness can be expressed as (thickness of the sheet conductive material / D50 of the sheet conductive material)×100%.
[0092] By using such a planar conductive material, the life characteristics of the lithium secondary battery are not significantly affected, and the number of points at which charging and discharging are possible increases, resulting in excellent output characteristics at a high C-rate.
[0093] In one embodiment of the present application, the linear conductive material may be a linear conductive material such as a carbon nanotube. The carbon nanotube may be a bundled carbon nanotube. The bundled carbon nanotube may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in the form of a bundle or rope in which a plurality of carbon nanotube units are arranged side by side or entangled with the longitudinal axes of the carbon nanotube units in substantially the same orientation. The carbon nanotube unit has a graphite sheet in the form of a cylinder with a nano-sized diameter and has an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure of the winding. The bundled carbon nanotube may be uniformly dispersed during the manufacture of the negative electrode compared to an entangled type carbon nanotube, and may smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.
[0094] In one embodiment of the present application, the linear conductive material may be SWCNT; or MWCNT.
[0095] In one embodiment of the present application, the linear conductive material may be SWCNT. In one embodiment of the present application, the linear conductive material may have an average particle size of 1 μm or more and 5 μm or less.
[0096] In one embodiment of the present application, the BET specific surface area of the linear conductive material is 500 m 2 / g or more 1500m 2 / g or less.
[0097] In one embodiment of the present application, the Raman IG / ID of the linear conductive material may be in the range of 100 or more and 150 or less.
[0098] The negative electrode conductive material according to the present application may contain, based on 100 parts by weight of the negative electrode conductive material, 90 parts by weight or more and 99.9 parts by weight or less of the sheet conductive material, and 0.1 parts by weight or more and 10 parts by weight or less of the linear conductive material.
[0099] In yet another embodiment, the negative electrode conductive material may contain, per 100 parts by weight of the negative electrode conductive material, 90 parts by weight or more and 99.9 parts by weight or less of the sheet conductive material; preferably 92 parts by weight or more and 99.9 parts by weight or less, and more preferably 93 parts by weight or more and 98 parts by weight or less.
[0100] In yet another embodiment, the negative electrode conductive material may contain 0.1 parts by weight or more and 10 parts by weight or less of the linear conductive material, preferably 0.1 parts by weight or more and 8 parts by weight or less, and more preferably 0.5 parts by weight or more and 7 parts by weight or less, based on 100 parts by weight of the negative electrode conductive material.
[0101] The negative electrode conductive material according to the present application is characterized by not containing dot-shaped conductive materials such as carbon black. When dot-shaped conductive materials are used, there is room for improving the life performance, but there is a limit, and when excessive dot-shaped conductive materials are used, the viscosity of the negative electrode slurry increases due to the high specific surface area of the dot-shaped conductive materials, which causes a problem of increasing the amount of gas generated at high temperatures.
[0102] Therefore, the negative electrode composition of the present application does not use a dot-like conductive material, but contains two types of conductive materials, a planar conductive material and a linear conductive material. By including the above-mentioned content, the viscosity of the negative electrode slurry containing it can be reduced, and the amount of high-temperature storage gas can be reduced.
[0103] In one embodiment of the present application, there is provided a negative electrode composition in which the linear conductive material has a volume resistance (Ω·cm@1 g / cc) of 0.0005 or more and 0.003 or less.
[0104] The linear conductive material satisfies the volume resistivity and has the characteristic of being able to improve the conductivity of the negative electrode containing the linear conductive material, that is, it corresponds to a factor indicating the electric network retention performance of the linear conductive material.
[0105] In one embodiment of the present application, there is provided a negative electrode composition in which the negative electrode conductive material is present in an amount of 10 parts by weight or more and 40 parts by weight or less, based on 100 parts by weight of the negative electrode composition.
[0106] In another embodiment, the negative electrode conductive material may comprise, based on 100 parts by weight of the negative electrode composition, 10 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 15 parts by weight or more and 25 parts by weight or less.
[0107] In one embodiment of the present application, the negative electrode conductive material includes a planar conductive material and a linear conductive material, each of which satisfies the above-mentioned composition and ratio, so that the battery does not have a significant effect on the life characteristics of existing lithium secondary batteries, and has many points at which charging and discharging are possible, resulting in excellent output characteristics at a high C-rate.
[0108] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and role different from that of a carbon-based active material generally used as a negative electrode active material. Specifically, the carbon-based active material used as a negative electrode active material may be artificial graphite or natural graphite, and refers to a material that is processed into a spherical or dot-like shape to facilitate the storage and release of lithium ions.
[0109] Meanwhile, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape and may be expressed as plate-like graphite. That is, it is a material contained in the negative electrode active material layer to maintain a conductive path, and does not play a role in storing and releasing lithium, but means a material for securing a planar conductive path inside the negative electrode active material layer.
[0110] That is, in the present application, the use of plate-shaped graphite as a negative electrode conductive material means that it is processed into a planar or plate-shaped form and is used as a material that ensures a conductive path, rather than serving to store or release lithium. In this case, the negative electrode active material contained therein has high capacity characteristics for storing and releasing lithium, and serves to store and release all the lithium ions transferred from the positive electrode.
[0111] Meanwhile, the use of a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and is used as a material that plays a role in storing or releasing lithium.
[0112] That is, the carbon-based active material, artificial graphite or natural graphite, has a BET specific surface area of 0.1 m 2 / g or more 4.5m 2 / g or less. In addition, the plate-shaped graphite, which is a planar conductive material, has a planar BET specific surface area of 5 m 2 / g or more.
[0113] The negative electrode conductive material according to the present application has a completely different structure from the conductive material applied to the positive electrode. That is, the negative electrode conductive material according to the present application plays a role of capturing the contact between the silicon-based active materials, which have a very large volume expansion of the electrodes due to charging and discharging, while the positive electrode conductive material plays a role of providing some conductivity while acting as a buffer when rolled, and has a completely different structure and role from the negative electrode conductive material of the present invention.
[0114] In addition, the negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has particles that are simply smaller than the active material, and therefore has the properties of improving output characteristics and imparting some electrical conductivity, and has a completely different structure and role from a negative electrode conductive material applied together with a silicon-based active material as in the present invention.
[0115] In one embodiment of the present application, the negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.
[0116] The negative electrode binder according to one embodiment of the present application plays a role in suppressing the active material and conductive material in order to prevent twisting and structural deformation of the negative electrode structure during volume expansion and relaxation of the silicon-based active material, and any common binder can be used as long as it fulfills the above role, and specifically, a water-based binder can be used, and more specifically, a PAM-based binder can be used.
[0117] In one embodiment of the present application, the negative electrode binder may comprise 30 parts by weight or less, preferably 25 parts by weight or less, and more preferably 20 parts by weight or less, based on 100 parts by weight of the negative electrode composition, and may comprise 5 parts by weight or more, or 10 parts by weight or more.
[0118] Compared to the existing carbon-based negative electrode, when the Si-based negative electrode is used, a water-based binder is applied in the above weight part, and a negative electrode conductive material having a low functional group content can be used. Due to the above characteristics, the negative electrode conductive material has hydrophobicity and excellent bonding strength between the conductive material and the binder.
[0119] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; and a negative electrode active material layer formed on one or both sides of the negative electrode current collector layer, the negative electrode active material layer comprising the negative electrode composition according to the present application.
[0120] 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a negative electrode active material layer 20 on one side of a negative electrode current collector layer 10 can be seen. Although FIG. 1 shows that the negative electrode active material layer is formed on one side, the negative electrode active material layer may be formed on both sides.
[0121] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, fine irregularities may be formed on the surface to strengthen the binding force of the negative electrode active material, and it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0122] In one embodiment of the present application, the negative electrode for a lithium secondary battery may be formed by applying a negative electrode slurry containing the negative electrode composition to one or both surfaces of a negative electrode current collector layer, and drying the applied slurry.
[0123] In one embodiment of the present application, there is provided a negative electrode composition having a viscosity of 1,000 cP or more and 6,000 cP or less.
[0124] In this case, the negative electrode slurry may include the above-mentioned negative electrode composition; and a slurry solvent.
[0125] In one embodiment of the present application, the solid content of the negative electrode slurry may be 5% or more and 40% or less.
[0126] In another embodiment, the solid content of the negative electrode slurry may be in the range of 5% to 40%, preferably 7% to 35%, and more preferably 10% to 30%.
[0127] The solid content of the negative electrode slurry may refer to the content of the negative electrode composition contained in the negative electrode slurry, and may refer to the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0128] When the solid content of the negative electrode slurry satisfies the above range, the viscosity during the formation of the negative electrode active material layer is appropriate, and the negative electrode active material layer can be efficiently formed by minimizing particle aggregation of the negative electrode composition. In addition, the negative electrode composition contains the specific conductive material described above, which can suppress an increase in viscosity and improve the dispersibility of the negative electrode slurry.
[0129] In one embodiment of the present application, the viscosity of the negative electrode slurry may be 1,000 cP or more and 8,000 cP or less.
[0130] In another embodiment, the viscosity of the negative electrode slurry may be in the range of 1,000 cP or more and 8,000 cP or less, preferably 1,500 cP or more and 6,000 cP or less, and more preferably 2,000 cP or more and 4,000 cP or less.
[0131] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.
[0132] However, the thickness may vary depending on the type and application of the negative electrode used, and is not limited thereto.
[0133] In one embodiment of the present application, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less.
[0134] In another embodiment, the porosity of the negative electrode active material layer may be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0135] The porosity varies depending on the composition and content of the silicon-based active material, conductive material, and binder contained in the negative electrode active material layer, and in particular, the silicon-based active material and conductive material according to the present application are contained in a specific composition and content to satisfy the above range, thereby providing an electrode having an appropriate range of electrical conductivity and resistance.
[0136] In one embodiment of the present application, there is provided a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
[0137] 2 is a diagram showing a laminated structure of a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode 100 for a lithium secondary battery including a negative electrode active material layer 20 on one side of a negative electrode current collector layer 10 can be seen, and a positive electrode 200 for a lithium secondary battery including a positive electrode active material layer 40 on one side of a positive electrode current collector layer 50 can be seen, and the negative electrode 100 for a lithium secondary battery and the positive electrode 200 for a lithium secondary battery are laminated with a separator 30 sandwiched therebetween.
[0138] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.
[0139] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0140] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0141] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 O2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and 0.01≦c2≦0.6 is satisfied); 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.6) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be metallic lithium (Li-metal).
[0142] In one embodiment of the present application, the positive electrode active material includes a lithium transition metal composite compound including nickel (Ni), cobalt (Co), and manganese (Mn), and the lithium transition metal composite compound includes single particles or secondary particles, and the average particle size (D50) of the single particles may be 1 μm or more.
[0143] For example, the average particle size (D50) of the single particles may be 1 μm or more and 12 μm or less, 1 μm or more and 8 μm or less, 1 μm or more and 6 μm or less, more than 1 μm and 12 μm or less, more than 1 μm and 8 μm or less, or more than 1 μm and 6 μm or less.
[0144] The single particle can have excellent particle strength even if it is formed with a small particle size having an average particle size (D50) of 1 μm or more and 12 μm or less. For example, the single particle can have a strength of 650 kgf / cm 2 When the particle is rolled with a force of 650 kgf / cm, the particle strength is 100 MPa to 300 MPa. 2 Even if the electrode is rolled with a strong force, the phenomenon of an increase in fine particles in the electrode due to particle cracking is mitigated, thereby improving the life characteristics of the battery.
[0145] The single particles may be prepared by mixing a transition metal precursor and a lithium source material and sintering the mixture. The secondary particles may be prepared by a method different from that of the single particles, and the composition of the secondary particles may be the same as or different from that of the single particles.
[0146] The method for forming the single particles is not particularly limited, but may generally be formed by over-firing at an elevated firing temperature. The single particles may be prepared by using additives such as grain growth promoters that are useful for over-firing, or by changing the starting material.
[0147] For example, the sintering is performed at a temperature at which single particles can be formed. In order to form the single particles, the sintering must be performed at a higher temperature than that at which the secondary particles are produced. For example, when the precursor composition is the same, the sintering must be performed at a temperature about 30°C to 100°C higher than that at which the secondary particles are produced. The sintering temperature for forming the single particles may vary depending on the metal composition in the precursor. For example, when a high-content nickel (High-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 80 mol% or more is to be formed as a single particle, the sintering temperature may be about 700°C to 1000°C, preferably about 800°C to 950°C. When the sintering temperature satisfies the above range, a positive electrode active material including single particles having excellent electrochemical properties may be produced. When the sintering temperature is less than 790°C, a positive electrode active material including a lithium transition metal composite compound in the form of secondary particles may be produced, and when it exceeds 950°C, sintering may occur excessively, and a layered crystal structure may not be formed properly, resulting in a decrease in electrochemical properties.
[0148] In this specification, the term "single particle" is used to distinguish it from conventional secondary particles formed by agglomeration of tens to hundreds of primary particles, and is a concept that includes a single particle consisting of one primary particle and a pseudo-single particle form that is an agglomeration of 30 or less primary particles.
[0149] Specifically, in the present invention, a single particle may be in the form of a single particle consisting of one primary particle or a pseudo-single particle which is an aggregate of 30 or less primary particles, and a secondary particle may be in the form of an aggregate of several hundred primary particles.
[0150] In one embodiment of the present application, the lithium transition metal composite compound serving as the positive electrode active material further includes secondary particles, and the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.
[0151] In the present invention, a single particle may be in the form of a single particle consisting of one primary particle or a quasi-single particle which is an aggregate of 30 or less primary particles, and a secondary particle may be in the form of an aggregate of several hundred primary particles.
[0152] The lithium transition metal composite compound may further include secondary particles. The secondary particles refer to a form formed by agglomeration of primary particles, and can be distinguished from the concept of single particles including a form of one primary particle, one single particle, or a pseudo-single particle which is an agglomeration of 30 or less primary particles.
[0153] The particle diameter (D50) of the secondary particles may be 1 μm to 20 μm, 2 μm to 17 μm, and preferably 3 μm to 15 μm. The specific surface area (BET) of the secondary particles is less than 0.05 m 2 / g~10m 2 / g, preferably 0.1m 2 / g~1m 2 / g, and more preferably 0.3m 2 / g~0.8m 2 / g.
[0154] In another embodiment of the present application, the primary particles are aggregates of primary particles, and the primary particles have an average particle size (D50) of 0.5 μm to 3 μm. Specifically, the secondary particles may be in the form of aggregates of several hundred primary particles, and the primary particles may have an average particle size (D50) of 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.
[0155] When the average particle size (D50) of the primary particles satisfies the above range, a single particle positive electrode active material having excellent electrochemical properties can be formed. If the average particle size (D50) of the primary particles is too small, the number of agglomerates of the primary particles forming the lithium nickel oxide particles increases, and the effect of suppressing particle cracking during rolling decreases. If the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles becomes long, which increases resistance and may decrease output characteristics.
[0156] According to a further embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles, so that the single particles can have excellent particle strength even when formed with a small particle size, and thus the increase in fine particles in the electrode due to particle cracking can be mitigated, thereby improving the life characteristics of the battery.
[0157] In one embodiment of the present application, the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles by 1 μm to 18 μm.
[0158] For example, the average particle size (D50) of the single particles may be 1 μm to 16 μm smaller, 1.5 μm to 15 μm smaller, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.
[0159] When the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles, for example, when the above range is satisfied, the single particles can have excellent particle strength even if they are formed with a small particle size, thereby mitigating the phenomenon of an increase in fine particles in the electrode due to particle cracking, and improving the life characteristics and energy density of the battery.
[0160] According to a further embodiment of the present application, the single particles are contained in an amount of 15 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material. The single particles may be contained in an amount of 20 parts by weight to 100 parts by weight, or 30 parts by weight to 100 parts by weight relative to 100 parts by weight of the positive electrode active material.
[0161] For example, the single particles may be included in an amount of 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more relative to 100 parts by weight of the positive electrode active material. The single particles may be included in an amount of 100 parts by weight or less relative to 100 parts by weight of the positive electrode active material.
[0162] When the single particles are contained in the above range, excellent battery characteristics can be exhibited in combination with the above-mentioned negative electrode material. In particular, when the single particles are 15 parts by weight or more, the increase in fine particles in the electrode due to particle cracking during rolling after electrode preparation can be mitigated, thereby improving the life characteristics of the battery.
[0163] In one embodiment of the present application, the lithium composite transition metal compound may further include secondary particles, and the secondary particles may be 85 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less relative to 100 parts by weight of the positive electrode active material. The secondary particles may be 0 parts by weight or more relative to 100 parts by weight of the positive electrode active material.
[0164] When the above range is satisfied, the above-mentioned effect due to the presence of the single particle positive electrode active material can be maximized. When the secondary particle positive electrode active material is included, the component may be the same component as exemplified in the above-mentioned single particle positive electrode active material, or may be a different component, and may mean a form in which the single particle form is aggregated.
[0165] In one embodiment of the present application, the positive electrode active material in 100 parts by weight of the positive electrode active material layer may be contained in an amount of 80 parts by weight or more and 99.9 parts by weight or less, preferably 90 parts by weight or more and 99.9 parts by weight or less, more preferably 95 parts by weight or more and 99.9 parts by weight or less, and still more preferably 98 parts by weight or more and 99.9 parts by weight or less.
[0166] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0167] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.
[0168] The positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.
[0169] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.
[0170] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in manufacturing lithium secondary batteries, but are not limited to these. Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0171] Examples of the non-aqueous organic solvent include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0172] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, can be preferably used since they have a high dielectric constant as a high-viscosity organic solvent and dissociate lithium salts well. When such a cyclic carbonate is mixed with a low-viscosity, low-dielectric-constant chain carbonate such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore, it can be used more preferably.
[0173] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of:
[0174] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride for the purposes of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.
[0175] According to an embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate-limiting characteristics and high cycle characteristics, and therefore can be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system. EXAMPLES
[0176] In the following, preferred embodiments are presented to help understand the present invention, but the embodiments are merely illustrative of the present invention, and it is clear to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present invention. It is natural that such changes and modifications fall within the scope of the appended claims.
[0177] <Production Example> <Example 1> Anode manufacturing Silicon-based active material was formed by vaporizing silicon blocks of MG-Si with silane and then depositing them on a substrate after chemical reaction. At this time, the crystal grain size of the silicon-based active material could be controlled by controlling the process conditions (temperature condition 800℃~1100℃, pressure condition 10pa~150pa range), and as a result, a silicon-based active material with a crystal grain size of 62nm was produced.
[0178] Then, the silicon-based active material (Si, average particle size (D50): 3.5 μm, crystal grain size 62 nm), the first conductive material, the second conductive material, and polyacrylamide as a binder were mixed in a weight ratio of 80:9.6:0.4:10 to form a negative electrode composition, which was then added to distilled water as a solvent for forming a negative electrode slurry to prepare a negative electrode slurry.
[0179] The first conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm, thickness to D50 ratio 28%), and the second conductive material is SWCNT (number of layers: 1ea, average particle size: 1.6 μm, BET 1160m 2 / g, IG / ID ratio: 143).
[0180] As a specific mixing method, the conductive material, binder and water were dispersed using a homomixer at 2500 rpm for 30 minutes, and then the silicon-based active material was added and dispersed at 2500 rpm for 30 minutes to prepare a negative electrode slurry.
[0181] The negative electrode current collector layer was made of a copper current collector (thickness: 8 μm) and the negative electrode slurry was applied to both sides of the copper current collector at a rate of 85 mg / 25 cm. 2 The mixture was coated with a loading amount of 1000 g, rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 33 μm), which was used as a negative electrode (negative electrode thickness: 41 μm, negative electrode porosity: 40.0%).
[0182] <Example 2> In Example 1, the silicon chunks of MG-Si were gasified with silane, and then chemically reacted with the gas, followed by deposition on a substrate to form a silicon-based active material. The same procedure as in Example 1 was repeated, except that the crystal grain size of the silicon-based active material was controlled by controlling the process conditions (temperature condition: 800°C to 1100°C, pressure condition: 10 Pa to 150 Pa), and as a result, a silicon-based active material with a crystal grain size of 30 nm was produced.
[0183] <Example 3> In Example 1, the silicon chunks of MG-Si were gasified with silane, and then chemically reacted with the gas, followed by deposition on a substrate to form a silicon-based active material. The same procedure as in Example 1 was repeated, except that the crystal grain size of the silicon-based active material was controlled by controlling the process conditions (temperature condition: 800°C to 1100°C, pressure condition: 10 Pa to 150 Pa), and as a result, a silicon-based active material with a crystal grain size of 90 nm was produced.
[0184] <Comparative Example 1> In Example 1, the cooling and gas deposition environment was changed when preparing the silicon block MG-Si. Then, physical force was applied to crush the silicon block, and as a result, a silicon-based active material with a crystal grain size of 212 nm was prepared. A negative electrode was prepared in the same manner as in Example 1, except that a silicon-based active material with the above crystal grain size was used.
[0185] <Comparative Example 2> The negative electrode composition was prepared in the same manner as in Example 1, except that the silicon-based active material (Si, average particle size (D50): 3.5 μm, crystal grain size: 62 nm), dot-shaped conductive material (carbon black), and polyacrylamide as a binder were used in a weight ratio of 80:10:10.
[0186] <Comparative Example 3> The negative electrode composition was prepared in the same manner as in Example 1, except that the silicon-based active material (Si, average particle size (D50): 3.5 μm, crystal grain size: 62 nm), the first conductive material, and polyacrylamide as a binder were used in a weight ratio of 80:10:10 to form a negative electrode composition.
[0187] <Comparative Example 4> The negative electrode composition was prepared in the same manner as in Example 1, except that the silicon-based active material (Si, average particle size (D50): 3.5 μm, crystal grain size: 62 nm), the second conductive material, and polyacrylamide as a binder were used in a weight ratio of 84:0.5:15.5.
[0188] <Comparative Example 5> A negative electrode was produced in the same manner as in Example 1, except that a dot-like conductive material (carbon black) was used as the conductive material instead of the first conductive material.
[0189] <Comparative Example 6> The negative electrode composition was prepared in the same manner as in Example 1, except that the silicon-based active material (Si, average particle size (D50): 3.5 μm, crystal grain size: 62 nm), dot-shaped conductive material (carbon black), first conductive material, and polyacrylamide as a binder were used in a weight ratio of 80:5:5:10.
[0190] <Secondary battery manufacturing> LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).
[0191] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) and the positive electrode slurry was applied to both sides at 537 mg / 25 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).
[0192] An electrolyte was injected between the positive electrode and the negative electrode of the example or comparative example via a polyethylene separator to prepare a lithium secondary battery.
[0193] The electrolyte was an organic solvent mixture of fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) in a volume ratio of 30:70, to which vinylene carbonate was added at 3 wt% based on the total weight of the electrolyte, and LiPF6 was added as a lithium salt at a concentration of 1M.
[0194] <Experimental Example> Experimental example 1: Life evaluation The lithium secondary batteries including the negative electrodes prepared in the Examples and Comparative Examples were subjected to a life evaluation using an electrochemical charger / discharger to evaluate the capacity retention. The secondary batteries were subjected to an in-situ cycle test at 4.2-3.2V 1C / 1C, and the capacity retention was measured by charging / discharging at 1C / 1C (4.2-3.2V) every 50 cycles during the test. The results are shown in Table 1. Capacity retention rate (%) = {(discharge capacity at Nth cycle) / (discharge capacity at 1st cycle)} x 100
[0195] Experimental example 2: Resistance increase rate measurement evaluation In the test of Experimental Example 1, the capacity retention was measured by charging / discharging at 0.33C / 0.33C (4.2-3.0V) every 50 cycles, and then the resistance was measured by discharging at 2.5C pulse at SOC50, and the resistance increase rate was compared and analyzed. The results are shown in Table 1 below.
[0196] Experimental Example 3: Volume change due to gas generation using the pouch test A pouch cell having a capacity of 1 Ah for the lithium secondary battery including the negative electrode prepared in the Examples and Comparative Examples was fully charged to 4.2 V at 0.33 C and then stored in an oven at 60° C. for 8 weeks. After fully discharging to 2.5 V, the gas generated in the pouch cell was extracted by GC / MS and quantitatively analyzed for the gas. The results are shown in Table 1 below.
[0197] [Table 1]
[0198] As can be seen from the above examples and comparative examples, the negative electrode composition of the present invention uses a specific range of crystalline silicon-based active material to prepare a negative electrode in order to increase the energy density. In this case, the negative electrode conductor uses a planar conductor and a linear conductor to greatly improve the electrical connectivity between the silicon-based active materials, and as a result, it has been confirmed that the electrical isolation phenomenon that may occur when charging / discharging a negative electrode using a silicon-based active material is prevented, thereby improving the life of the negative electrode.
[0199] In the case of Comparative Example 1, the crystal grain size was outside the range of the present application, and it was confirmed that the strength of the silicon-based active material itself was reduced, making it difficult to provide flexibility when contained in the electrode, and that the volume expansion could not be suppressed, resulting in a decrease in life performance and an increase in resistance.
[0200] In the case of Comparative Example 2, an excessive amount of dot-shaped conductive material was contained, and although there was room for improvement in life performance, a high resistance increase rate was observed, and problems occurred in that the viscosity of the composition increased and the amount of high-temperature gas generated increased due to the high specific surface area.
[0201] In addition, in the case of Comparative Examples 3 to 6, the crystal grain size is the same, but in the case where planar and linear conductive materials are not used as in the present invention, it was confirmed that even in these cases, electrical connectivity could not be ensured, the life performance decreased, and the resistance increase rate was high.
[0202] Of these, Comparative Examples 2, 5 and 6 are cases where dot-shaped conductive material was used alone, and cases where dot-shaped and linear or dot-shaped and planar conductive materials were used in combination. It was found that by including dot-shaped conductive material, the amount of gas generated at high temperatures was higher than in the other examples and comparative examples.
[0203] That is, the negative electrode composition according to the present application is characterized in that a system that can be applied together with a high energy density silicon-based active material is constructed by applying the specific composition and content of the negative electrode conductive material as described above. [Explanation of symbols]
[0204] 10 Negative electrode current collector layer 20...Negative electrode active material layer 30...Separation membrane 40...Cathode active material layer 50 Positive electrode current collector layer 100 ···Negative electrode for lithium secondary battery 200 ···Positive electrode for lithium secondary batteries
Claims
1. A negative electrode composition comprising a silicon-based active material, a negative electrode conductive material, and a negative electrode binder, The silicon-based active material includes at least one selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and the silicon-based active material includes 70 parts by weight or more of the SiOx (x=0) based on 100 parts by weight of the silicon-based active material; The silicon-based active material has a crystal grain size of 200 nm or less, The negative electrode composition, wherein the negative electrode conductive material includes a sheet conductive material and a linear conductive material.
2. The negative electrode active material according to claim 1 , wherein the crystal grain size of the silicon-based active material is 10 nm or more and 150 nm or less.
3. 2. The negative electrode composition of claim 1, wherein the silicon-based active material has a D50 particle size of 3 μm or more and 10 μm or less.
4. The surface area of the silicon-based active material is 0.25 m 2 The negative electrode composition according to claim 1 , wherein the silicon-based active material has a molecular weight of 1.0 to 1.0 g / g or more.
5. The negative electrode composition according to claim 1 , wherein the viscosity of the negative electrode composition is 1,000 cP or more and 6,000 cP or less.
6. The negative electrode composition according to claim 1 , wherein the silicon-based active material is present in an amount of 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.
7. The negative electrode composition according to claim 1 , wherein the negative electrode conductive material is present in an amount of 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the negative electrode composition.
8. 2. The negative electrode composition according to claim 1, wherein the negative electrode conductive material comprises, per 100 parts by weight of the negative electrode conductive material, 90 parts by weight or more and 99.9 parts by weight or less of the sheet conductive material and 0.1 parts by weight or more and 10 parts by weight or less of the linear conductive material.
9. 2. The negative electrode composition according to claim 1, wherein the sheet conductive material has a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 6.0 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.
10. A negative electrode current collector layer; and A negative electrode active material layer comprising the negative electrode composition according to any one of claims 1 to 9, formed on one or both sides of the negative electrode current collector layer; A negative electrode for a lithium secondary battery comprising:
11. The thickness of the negative electrode current collector layer is 1 μm or more and 100 μm or less, 11. The negative electrode for a lithium secondary battery according to claim 10, wherein the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.
12. Positive electrode; The negative electrode for a lithium secondary battery according to claim 10; A separator disposed between the positive electrode and the negative electrode; and Electrolyte; A lithium secondary battery comprising:
Citation Information
Patent Citations
Lithium secondary cell and fabrication method thereof
JP2008034352A
Lithium secondary battery and its manufacturing method
JP2009245773A
Method for producing negative electrode active material for nonaqueous electrolyte secondary battery, negative electrode active material for nonaqueous electrolyte secondary battery, negative electrode material for nonaqueous electrolyte secondary battery, negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2012009421A
Silicon-containing particle, negative electrode material for nonaqueous electrolyte secondary battery using the same, nonaqueous electrolyte secondary battery, and method for producing silicon-containing particle
JP2014032880A
Positive electrode mixture and secondary battery containing the same
JP2018523281A